La limitación del acceso a la justicia penal de un Juez de la Corte Constitucional, que no puede ser objeto de una denuncia por un ciudadano afectado por la comisión de un delito, viola el principio constitucional de igualdad ante la ley - Jiménez Torres, Washington Oswaldo (2016)
The top-right of equality before the law is constitutionally guaranteed, it can not be violated, or else must apply to other valuation principle as the weighting, so, Article 186, paragraph 2 of the Law of Guarantees Jurisdictional and Constitutional Control of Ecuador states: "... criminal liability for offenses committed during and at the time of the functions performed in the judiciary, shall be subject to complaint, investigation and prosecution solely by the Attorney General or the State ... ". This clause violates the constitutional principle of equality before the law enshrined in the Constitution in Article 11, paragraph 2 which states: "All people are equal and enjoy the same rights, duties and opportunities." And the violation of Article 66 paragraph 4 of the Constitution on the rights of freedom which states: "The right to formal equality, substantive equality ..." and limiting access to criminal justice against a judge of the Court Constitution, which is not subject of a complaint by a citizen concerned for the commission of a crime, since according to the Organic Law of Guarantees Jurisdictional and Constitutional Control if the Attorney General does not file a complaint, no one can do, just as in The Constitution sets out the responsibilities of these judges, and no evidence that only the Attorney General may file a complaint against them, therefore there is a rule that goes against the Constitution, since the Attorney General can only report, this restricts the constitutional principle of equality before the law, because a citizen can not sue a judge of the Constitutional Court for an offense, ie the complaint, investigation and prosecution only, is exclusive of the Attorney General. - There is also a legal problem in this case a standard (Law of Guarantees Jurisdictional and Constitutional Control) that goes against the Constitution, since it violates the principle of equality before the law and the right to freedom of formal and material equality.